2016
DOI: 10.1016/j.stemcr.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblasts Derived from Hepatic Progenitor Cells Create the Tumor Microenvironment

Abstract: SummaryHepatic progenitor cells (HPCs) appear in response to several types of chronic injury in the human and rodent liver that often develop into liver fibrosis, cirrhosis, and primary liver cancers. However, the contribution of HPCs to the pathogenesis and progression of such liver diseases remains controversial. HPCs are generally defined as cells that can differentiate into hepatocytes and cholangiocytes. In this study, however, we found that HPCs isolated from the chronically injured liver can also give r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Moreover, growth factors and chemokines produced by cancer and endothelial cells promote stromal fibroblast activation, infiltration of T lymphocytes, macrophage activation and fibroblasts differentiation into myofibroblasts and cancer associated fibroblasts (CAFs) [28]. Myofibroblasts and CAFs, found in the stroma of carcinomas and especially in the tumor invasive edge, secrete ECM proteins, cytokines, growth factors, chemokines, hormones and inflammation proteins, thus promoting cancer cell proliferation and CSCs de-differentiation and migration [29,30]. The main contribution of CAFs and myofibroblasts to tumor microenvironment is therefore the synthesis and release of significant amounts of ECM proteins; newly deposited collagen and elastin fibers, in fact, are reoriented and remodeled to generate larger, more-rigid fibrils that contribute to the tumor-surrounding ECM special features [31,32].…”
Section: The Tumor Microenvironment and Ecm Modificationsmentioning
confidence: 99%
“…Moreover, growth factors and chemokines produced by cancer and endothelial cells promote stromal fibroblast activation, infiltration of T lymphocytes, macrophage activation and fibroblasts differentiation into myofibroblasts and cancer associated fibroblasts (CAFs) [28]. Myofibroblasts and CAFs, found in the stroma of carcinomas and especially in the tumor invasive edge, secrete ECM proteins, cytokines, growth factors, chemokines, hormones and inflammation proteins, thus promoting cancer cell proliferation and CSCs de-differentiation and migration [29,30]. The main contribution of CAFs and myofibroblasts to tumor microenvironment is therefore the synthesis and release of significant amounts of ECM proteins; newly deposited collagen and elastin fibers, in fact, are reoriented and remodeled to generate larger, more-rigid fibrils that contribute to the tumor-surrounding ECM special features [31,32].…”
Section: The Tumor Microenvironment and Ecm Modificationsmentioning
confidence: 99%
“…In a recent study, Sekiya et al have shown that HPCs isolated from mice injured liver can differentiate into myofibroblasts, as a third distinct cell type, in addition to hepatocyte and cholangiocyte differentiation. They also have proposed that HPCs can contribute to the formation of the premalignant niche by abundant production of myofibroblasts [35].…”
Section: Fibrocytesmentioning
confidence: 99%
“…32 Previous reports have also shown that HPCs can serve as a source of MFs that may create a microenvironment for tumour development arising through the progression of chronic liver injury. 33 Our in vivo and in vitro experiments showed that HPCs differentiate into MFs via the action of LPS. Meanwhile, hepatobiliary differentiation was inhibited, indicating that HPCs aggravate liver fibrosis due to their abnormal differentiation into MFs under the influence of LPS.…”
Section: Discussionmentioning
confidence: 75%